Premature mortality attributable to COVID-19: potential years of life lost in 17 countries around the world, January–August 2020 (2022)
Background: Understanding the impact of the burden of COVID‐19 is key to successfully navigating the COVID‐19 pandemic. As part of a larger investigation on COVID‐19 mortality impact, this study aims to estimate the Potential Years of Life Lost (PYLL) in 17 countries and territories across the world (Australia, Brazil, Cape Verde, Colombia, Cyprus, France, Georgia, Israel, Kazakhstan, Peru, Norway, England & Wales, Scotland, Slovenia, Sweden, Ukraine, and the United States [USA]). Methods: Age‐ and sex‐specific COVID‐19 death numbers from primary national sources were collected by an inter‐ national research consortium. The study period was established based on the availability of data from the inception of the pandemic to the end of August 2020. The PYLL for each country were computed using 80 years as the maximum life expectancy. Results: As of August 2020, 442,677 (range: 18–185,083) deaths attributed to COVID‐19 were recorded in 17 coun‐ tries which translated to 4,210,654 (range: 112–1,554,225) PYLL. The average PYLL per death was 8.7 years, with substantial variation ranging from 2.7 years in Australia to 19.3 PYLL in Ukraine. North and South American countries as well as England & Wales, Scotland and Sweden experienced the highest PYLL per 100,000 population; whereas Australia, Slovenia and Georgia experienced the lowest. Overall, males experienced higher PYLL rate and higher PYLL per death than females. In most countries, most of the PYLL were observed for people aged over 60 or 65 years, irrespective of sex. Yet, Brazil, Cape Verde, Colombia, Israel, Peru, Scotland, Ukraine, and the USA concentrated most PYLL in younger age groups. Conclusions: Our results highlight the role of PYLL as a tool to understand the impact of COVID‐19 on demographic groups within and across countries, guiding preventive measures to protect these groups under the ongoing pan‐ demic. Continuous monitoring of PYLL is therefore needed to better understand the burden of COVID‐19 in terms of premature mortality.